If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -32 = 6 + c Solving -32 = 6 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -32 + -1c = 6 + c + -1c Combine like terms: c + -1c = 0 -32 + -1c = 6 + 0 -32 + -1c = 6 Add '32' to each side of the equation. -32 + 32 + -1c = 6 + 32 Combine like terms: -32 + 32 = 0 0 + -1c = 6 + 32 -1c = 6 + 32 Combine like terms: 6 + 32 = 38 -1c = 38 Divide each side by '-1'. c = -38 Simplifying c = -38
| [7x-4]+8=3 | | 8(5-s)/5=2s | | -8(2x+1)=36 | | 36.4+(9.2-4.9/7) | | 17x+1+12x+5=180 | | 11/2+9/2 | | 9x-x^2+6=0 | | 2l-3=5 | | 8(2x+1)=36 | | (m+5)+8= | | X/4-4=3x/4-61 | | -5-4-2= | | y=1.25x+8.75 | | ?x-1=x-21 | | 4.3t+2.1t= | | [6x-9]+5=2 | | 1/4y-3=18 | | 2/3=3t/4+3 | | (19/5)+6x=(26/5) | | 2=-10x | | 2x(-3)-15= | | (6-7)+2= | | 2x(-5)-15= | | 5y-3y= | | 12=-9+y | | 5x+4=5x-5 | | 4(x-5)+5=3x-6-x | | -3x=4(3x-2)1 | | 5+(-4)+(-2)= | | 22(17.8)+70=17(17.8)-95 | | 34+3v=6(v+6)+4 | | 5[x-3]=20 |